Constant-Quality House Price Indexes for Switzerland - Steven C. Bourassa; Martin Hoesli; Donato Scognamiglio; Philippe Sormani (Swiss Journal of Economics and Statistics, 2008)
The measurement of house price movements is a vital topic from both academic and practical perspectives and hence has been the focus of much research. There is almost unanimous consensus in the literature that house price indexes should control for the quality of properties; the most widely used methods to attain this aim are the hedonic and repeat sales approaches. The objective of this paper is to compare the Swiss house prices indexes published by the Swiss National Bank (SNB), which are constructed using medians of list prices as published in newspapers and on the internet, to hedonic indexes based on sale prices for the period 1985 to 2006. We find that the list price indexes exhibit quite a different price path than the hedonic indexes during the period. In particular, they appear to overstate price changes in housing markets. We attribute this, at least in part, to changes over time in the composition of the sample of properties on the market.
Keywords: E31; R31; 330; house price indexes; hedonic method; Switzerland